COMMUNITY ENGAGEMENT: USM, CHIANG MAI UNIVERSITY DONATE BOOKS TO FOUR SCHOOLS IN THAILAND - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
CHIANG MAI (THAILAND), June 2015 Universiti Sains Malaysia (USM) joined hands with Chiang Mai University (CMU) to donate English educational books to four schools in Thailand that are involved in community health programmes at the Saraphi Hospital here recently.